Emerging Perspectives of Bone Metastasis in Hepatocellular Carcinoma - Yuan, Xiaofeng; Zhuang, Ming; Zhu, Xi; Cheng, Dong; Liu, Jie; Sun, Donglin; Qiu, Xubin; Lu, Yunjie; Sartorius, Kurt (Frontiers in Oncology, 2022)
Recent evidence suggests the global incidence and mortality of hepatocellular carcinoma (HCC) is increasing. Although the highest incidence of HCC remains entrenched in WHO regions with high levels of HBV-HCV infection, the etiology of this disease is rapidly changing to include other lifestyle risk factors. Extrahepatic metastasis is a frequent feature of advanced HCC and most commonly locates in the lungs and bone. Bone metastasis in HCC (HCC-BM) signals a more aggressive stage of disease and a poorer prognosis, simultaneously HCC-BM compromises the function and integrity of bone tissue. HCC induced osteolysis is a prominent feature of metastasis that complicates treatment needed for pathologic fractures, bone pain and other skeletal events like hypercalcemia and nerve compression. Early detection of bone metastases facilitates the treatment strategy for avoiding and relieving complications. Although recent therapeutic advances in HCC like targeting agents and immunotherapy have improved survival, the prognosis for patients with HCC-BM remains problematic. The identification of critical HCC-BM pathways in the bone micro-environment could provide important insights to guide future detection and therapy. This review presents an overview of the clinical development of bone metastases in HCC, identifying key clinical features and identifying potential molecular targets that can be deployed as diagnostic tools or therapeutic agents.